Beyond ecodesign, internationalized markets enhance the global warming potential in the wood furniture sector. (15th December 2022) - Coloma-Jiménez, Maider; Akizu-Gardoki, Ortzi; Lizundia, Erlantz
Abstract: Circular Economy principles encourage the implementation of bio-based and renewable materials over non-renewable technical counterparts. Wood-based materials can effectively address finite resource depletion and the accumulation of non-biodegradable waste into terrestrial and marine environments. In this context, the furniture industry has long relied on the use of wood for manufacture goods. However, the use of renewable materials is not directly translated into sustainable consumer goods. Accordingly, this work analyzes the life cycle environmental impacts of an eco-designed and locally-manufactured wooden bunk bed and compares local and international market scenarios to understand its cradle-to-grave environmental footprint. Using primary data, the life cycle assessment (LCA) methodology is followed to quantify and compare the environmental impacts of a currently commercially available wooden bunk bed over alternative scenarios. To facilitate future comparison, 1 kg of furniture is used as a functional unit. The cradle-to-grave system boundaries are established according to the reference "Furniture, except seats and mattresses" Product Category Rule. The upstream, core and downstream life-cycle stages are considered, and the environmental impacts are presented into eight different categories. To provide the bigger picture, obtained results are compared with literature. A cradle-to-grave CO2 -eq footprint of 1.71 kg per kg of an already eco-designed bunk bed is obtained, 15.1% below average traditional furniture. The downstream stage contributes to the 58.3% of the total greenhouse gas emissions, while the upstream and core phases present a share of 26.2% and 15.5%, respectively. Such a large contribution of the downstream phase originates from the transportation to the final customer (82.6% of this phase). For upstream and core phases, plywood production (53.1% share during the upstream ) and electricity consumption (75.1% share during the core ) are the main hotspots. Furthermore, this work quantifies the global warming potential of current internationalized wood furniture markets. Local furniture sale can reduce the CO2 emissions of the wooden bunk bed by 40%. Instead, selling the bed abroad involves a CO2 emission increase of 59%, while raw material importation enhances the impacts by 39–45%. The adoption of local production and consumption patterns emerge the most effective measures to reduce the environmental impacts of the furniture industry as the purchase of an overseas manufactured wood bunk increases the emissions by 79%. This research aims not only to bring light in the scientific community in LCA calculations but also help producers and consumers in the transition towards more sustainable consumption and production patterns in the wooden furniture market. Graphical abstract: Image 1 Highlights: The life cycle environmental impacts of a wooden bunk bed are studied to identify impact hotspots. Primary data is used to conduct a cradle-to-grave life cycle assessment following Product Category Rules. A CO2 -eq footprint of 1.71 kg per kg of an eco-designed bunk bed is obtained. For upstream and core phases, plywood production and electricity consumption are the main hotspots. 4 alternative scenarios are analyzed so the role of local manufacturing and selling on the overall impacts is understood.